(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article investigates the impact of social media comparisons on the psychological well-being of adolescents and young adults. Exposure to idealized content, peer comparisons, and online validation affects self-esteem, anxiety, and depressive symptoms. Results indicate that excessive social comparison reduces psychological well-being, whereas mindful use and digital literacy mitigate these effects.